The Impacts of CIAT’s Collaborative Research - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2017)
The International Center for Tropical Agriculture (CIAT) is celebrating 50 years of collaborative work with hundreds of partners across the tropics. During 50 years, CIAT has led the development and dissemination of technologies, innovative methods, and new knowledge that better enable farmers to enhance eco-efficiency in agriculture and contribute to building a sustainable food future. CIAT scientists have compiled an impressive record of achievements. In the interests of accountability to donors and other stakeholders, and to help lead the Center’s strategic research investments, they have also devoted considerable effort to measure the economic impact of their work. This document reports some of the main impacts of CIAT’s collaborative research, highlights key initiatives whose impacts have yet to be assessed, and describes several new studies and other efforts aimed to strengthen capacity for economic analysis.